Kewenangan Anak Tertua Dalam Pembagian Harta Waris (Studi Di Desa Bagendang Permai Kecamatan Mentaya Hilir Utara Kabupaten Kotawaringin Timur) - Dedy Dedy (Jurnal Studi Agama dan Masyarakat, 2016)
The background of the authority Elder Son In Divisonof property inheritance at the village of Bagendang Permai district at MentayaHilir Utara of East Kotawaringin, the basis of the authority of Elder Son In Divison was entrusted to distributed the property inheritance at village BagendangPermai district of MentayaHilir Utara of East Kotawaringin, the implementation of the distribution  property inheritance by the oldest child of his/her family at the village of Bagendang Permai of the district Mentaya Hilir Utara of East Kotawaringin. This study used qualitative descriptive method which collected data derived from the words obtained in observation, interviews, and documentation, subjects were 10 family. The results showed that the oldest child has an obligation to distribute the property inheritance owned by parents to each heir is the right to receive. The basicof authority  was entrusted by oldest child to distribute of the property inheritance, because the mandater entrusted by their parents elder son In Divison to distribute left to heirs. The impelementation of the distribution of property inheritance by the eldostchild to his/her family at the village of BagendangPermai, the family gathered for deliberation to distribute the properti inheritance owned by their parents were led by Elder Son in the family.